أثر استخدام برنامج تعليمي حاسوبي في تنمية مهارة الاستماع النشط دراسة شبه تجريبية على عينة من أطفال رياض الأطفال في محافظة اللاذقية - بوبو منذر; أحمد مطيعة; حجة رنا (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
يهدف البحث إلى الكشف عن أثر استخدام برنامج تعليمي حاسوبي في تنمية مهارة الاستماع لدى أطفال الرياض، ولتحقيق ذلك تم اعتماد منهج شبه تجريبي بتصميم المجموعتين. وقد قامت الباحثة بتصميم برنامج تعليمي حاسوبي وعرضه على أطفال المجموعة التجريبية في حين لم يتم عرضه على المجموعة الضابطة. تم استخدام اختبار تحصيلي وبطاقة ملاحظة تجيب عليها معلمات الرياض لتحقيق أهداف الدراسة، بعد التحقق من صدق الاختبار وثباته تم تطبيقه على عينتي الدراسة التجريبية (18 طفلاً وطفلة) والضابطة (18 طفلاً وطفلة). استخدمت الباحثة الإحصاء اللامعلمي لدراسة الفروق بين متوسط تحصيل الأطفال في كل من المجموعة التجريبية والمجموعة الضابطة على الاختبار التحصيلي، وقد أظهرت نتائج البحث وجود فروق بين متوسط تحصيل أطفال المجموعة التجريبية ومتوسط أطفال المجموعة الضابطة على الاختبار البعدي لصالح المجموعة التجريبية. كما تبين عدم وجود فروق بين متوسطي تحصيل الأطفال الذكور والإناث في المجموعة التجريبية، وبين البحث عدم وجود فروق بين متوسطي تحصيل درجات أطفال المجموعة التجريبية على الاختبارين البعدي والمؤجل. The study aims to reveal the effect of using a computer-educational program in the development of the listening skill of kindergarten children. To achieve this, a semi-experimental approach has been adopted to design the groups. The researcher has designed a computerized educational program and presented it to the children in the experimental group while not being presented to the control group. An achievement test and card notes were presented to be answered by kindergarten’s teachers to achieve the objectives of the study. After the verification of the test, its sincerity and persistence has been applied to samples of the experimental group (18 boys and girls) and control group (18 boys and girls). The researcher used Non-Parametric statistics to study the differences between the average collection of children’s achievement test. The results of the study showed the existence of differences between the average achievement of the experimental group and the control group average kids on the post-test. It also showed no differences between the averages of the mean scores of male and female children in the experimental group. The research showed the absence of differences between the average achievement of the experimental group on the post-test and the delayed tests.